2014
DOI: 10.1371/journal.pone.0112749
|View full text |Cite
|
Sign up to set email alerts
|

An AGM Model for Changes in Complement during Pregnancy: Neutralization of Influenza Virus by Serum Is Diminished in Late Third Trimester

Abstract: Pregnant women in the third trimester are at increased risk of severe influenza disease relative to the general population, though mechanisms behind this are not completely understood. The immune response to influenza infection employs both complement (C′) and antibody (Ab). The relative contributions of these components to the anti-viral response are difficult to dissect because most humans have pre-existing influenza-specific Abs. We developed the African green monkey (AGM) as a tractable nonhuman primate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…This study was consistent with an earlier study by Richani demonstrating increased C3a and C5a during pregnancy (Richani et al, 2005). In contrast, in an African green monkey model of influenza during pregnancy, investigators found that C3, C3a and C4 were actually decreased late in gestation compared to non pregnant animals, correlating with decreased viral neutralization and influenza susceptibility late in pregnancy (Mayer and Parks, 2014). Clearly when considering complement and its activation in adverse pregnancy outcomes, a gestationally matched control group of pregnant women with no adverse outcomes must be used rather than simply using non-pregnant controls.…”
Section: Complement System and Normal Pregnancymentioning
confidence: 97%
“…This study was consistent with an earlier study by Richani demonstrating increased C3a and C5a during pregnancy (Richani et al, 2005). In contrast, in an African green monkey model of influenza during pregnancy, investigators found that C3, C3a and C4 were actually decreased late in gestation compared to non pregnant animals, correlating with decreased viral neutralization and influenza susceptibility late in pregnancy (Mayer and Parks, 2014). Clearly when considering complement and its activation in adverse pregnancy outcomes, a gestationally matched control group of pregnant women with no adverse outcomes must be used rather than simply using non-pregnant controls.…”
Section: Complement System and Normal Pregnancymentioning
confidence: 97%
“…Influenza infection in the pregnant ferret model does show reduced IgG-specific B-cell responses after experimental infection, although it remains to be determined if this occurs during natural infection in humans (Yoon et al 2018). Interestingly, the complement pathway components C3, C3a, and C4 show diminished antibody-dependent neutralization of influenza in pregnant African green monkeys (Mayer and Parks 2014).…”
Section: Pregnancymentioning
confidence: 99%
“…This is in part due to a lack of animal models that recapitulate the natural progression of human IAV disease, endocrinology, and pregnancy. Nonhuman primates are an excellent model of pregnancy 319 and viral respiratory infections, [319][320][321][322][323][324][325] but most have differences in the hormonal cascade associated with parturition (labor onset). A combination of in vitro and in vivo models is necessary to dissect the complex interactions between sex hormones, pregnancy, and the pathogenesis of viral respiratory infections.…”
Section: Con Clus Ionsmentioning
confidence: 99%